THE NEEDS ANALYSIS FOR AMPLIFYING EXTRAMURAL ENGLISH LEARNING AMONG UNIVERSITY STUDENTS OF ENGLISH IN INDONESIA - Agus Darwanto; Ririn Sotyarini (Sekolah Tinggi Bahasa Asing LIA Yogyakarta, 2022)
ABSTRACT This research was to investigate rates of extramural English (EE) activities among college students of English in an EFL (English as a foreign language) context of Indonesia correlated with several factors such as perceived English competence, genders, and amount of use of different language skills. As many as 161 respondents from 7 English departments across Indonesia took part in this research by responding to a set of questionnaires developed in Google Forms and distributed to the student respondents through WhatsApp groups, emails, and Facebook with the help of their lecturers. The results indicate that first, all respondents did EE activities with various degrees of intensity with a similar pattern of choice activities across levels of students’ perceived English competence. Second, EE receptive skill activities were more frequently practiced than productive ones. When all skills are correlated against perceived competence, the reading showed the highest value of the correlation index (0.612). Reading activities also were the most practiced regardless of the level of competence. This research also found that male students were more active in EE use. Next, most respondents showed more frequency of online EE activities than offline ones. They did not, however, do much face-to-face (FTF) communication when outside the classroom. In this respect, providing more motivation and more frequency for virtual EE practice should be necessary to promote beyond EE use. School’s recognition of students’ EE activities thus beyond classroom learning, has to be enabled. This way, a composite model of formal-informal learning will help the process of the acquisition of English to the maximum. Keywords: out-of-class; extramural English; levels of competence; language skills; navigating skills